Research Supervisor: Between the Challenges of Time and the Realities of Higher Education - V. V. Zyryanov (Высшее образование в России, 2019)
The article was prepared using materials from expert interviews conducted within the framework of the grant of the President of the Russian Federation for the development of civil society “Development of a modern model for the formation of research competencies of graduates of educational programs in fundamental areas of training and higher education specialties”. In the context of research competencies formation, the article substantiates the relevance of the appeal to the figure of a research supervisor. In this regard, it is shown that research guidance is a determining element of science education. The author examines the tasks that supervisor fulfils, the qualities that he must possess for the successful solution of these problems, the functions carried out to solve them, as well as the conditions providing the normal course of research guidance and the limitations that impede it. Among the opportunities and limitations, the article highlights such factors as qualification of scientific leaders, their motivation, the style of research guidance. Based on the analysis, problems and contradictions in the process of implementing research guidance were identified. The author formulates proposals for solutions to overcome them.